Maintenance of lift systems affecting resident satisfaction in low-cost high-rise residential buildings - Au-Yong, Cheong Peng; Azmi, Nur Farhana; Mahassan, Nur Aaina (Emerald, 2018)
Purpose: Providing quality low-cost high-rise residential housing for poor households remains a major concern worldwide and especially in Malaysia. Despite government effort to maintain the quality of the housing through the Housing Maintenance Program and 1Malaysia Maintenance Fund Program (TP1M), the maintenance industry is still faced with serious housing quality problems in terms of facilities, one of which is the lift system. As the most expensive and important transportation system in a high-rise building, a lift system requires regular maintenance and inspection to provide safe and effective service to occupants. Unfortunately, most lift systems in Malaysia are not effectively maintained. The purpose of this paper is to examine contributing factors to the breakdown of lift systems, which greatly affect resident satisfaction in low-cost high-rise residential buildings. Design/methodology/approach: Semi-structured interviews were conducted with three stakeholders involved in maintenance management to identify the common causes of lift breakdown. Subsequently, a questionnaire survey was used to investigate resident satisfaction with the system. Findings: The results demonstrate vandalism as the most common cause for the frequent breakdown of lift system in low-cost housing. The study also reveals that there is a significant relationship between system breakdown rate and residents’ satisfaction. Originality/value: The paper concludes with the recommendation that stakeholders, including both maintenance personnel and residents, should commit themselves to ensuring that the use and care of lift system are correct.